2013
DOI: 10.1007/s11060-013-1313-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic repression of the dopamine receptor D4 in pediatric tumors of the central nervous system

Abstract: Epigenetic alterations are common events in cancer. Using a genome wide methylation screen (Restriction Landmark Genomic Scanning-RLGS) we identified the gene for the dopamine receptor D4 (DRD4) as tumor-specific methylated. As DRD4 is involved in early brain development and may thus be involved in developmentally dependent tumors of the CNS in children epigenetic deregulation of DRD4 and its functional consequences were analyzed in vitro. CpG methylation of DRD4 was detected in 18/24 medulloblastomas, 23/29 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Over-expression of SNCA or SNCAIP in GPCs has been shown to promote GPC proliferation and protection from apoptosis [49] [52] . Interestingly, a recent report describing epigenetic repression of the dopamine receptor family member, DRD4, in primary medulloblastoma adds further support for a significant role for deregulated dopamine signalling in medulloblastoma pathogenesis [53] . Additional novel findings from our analysis indicate that Group 4 medulloblastoma over-express semaphorin signalling molecules, including DPYSL3 and DPYSL4 , which regulate neuronal differentiation and apoptosis in the context of synaptic pruning [54] .…”
Section: Discussionmentioning
confidence: 93%
“…Over-expression of SNCA or SNCAIP in GPCs has been shown to promote GPC proliferation and protection from apoptosis [49] [52] . Interestingly, a recent report describing epigenetic repression of the dopamine receptor family member, DRD4, in primary medulloblastoma adds further support for a significant role for deregulated dopamine signalling in medulloblastoma pathogenesis [53] . Additional novel findings from our analysis indicate that Group 4 medulloblastoma over-express semaphorin signalling molecules, including DPYSL3 and DPYSL4 , which regulate neuronal differentiation and apoptosis in the context of synaptic pruning [54] .…”
Section: Discussionmentioning
confidence: 93%
“…However, DRD4 antagonists showed better selectivity for GNS in our screen compared with DRD2 antagonists (data not shown). Although epigenetic suppression of DRD4 has been reported in pediatric CNS tumors (Unland et al, 2013), DRD4 is not methylated in TCGA GBM samples, and mutations in the DRD5 and DRD3 genes occur in a small fraction of GBM samples (Brennan et al, 2013). Finally, we note that dopamine receptor antagonists may have activity against other cancer stem cell types, including leukemia (Sachlos et al, 2012) and lung cancer (Yeh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, EZH2 is a histone methyltransferase, which plays an important role in tumor development (Santos-Rosa and Caldas, 2005). Moreover, this protein might also play essential roles in the control of central nervous systems by regulating the dopamine receptor D4 (Unland et al, 2014).…”
Section: Functionmentioning
confidence: 99%
“…Their analyses suggested DRD4 as a direct target of EZH2. In particular, they showed that depletion of EZH2 is sufficient to induce re-expression of DRD4, suggesting the role of EZH2 for DNA hypermethylation in the epigenetic inhibition of DRD4 (Unland et al, 2014).…”
Section: Pediatric Tumors Of the Central Nervous Systemmentioning
confidence: 99%